Decadal shift in foraging strategy of a migratory southern ocean predator. (14th December 2020) - van den Berg, Gideon L.; Vermeulen, Els; Valenzuela, Luciano O.; Bérubé, Martine; Ganswindt, Andre; Gröcke, Darren R.; Hall, Grant; Hulva, Pavel; Neveceralova, Petra; Palsbøll, Per J.; Carroll, Emma L.
ABSTRACT: Rapid anthropogenic environmental change is expected to impact a host of ecological parameters in Southern Ocean ecosystems. Of critical concern are the consequences of these changes on the range of species that show fidelity to migratory destinations, as philopatry is hypothesized to help or hinder adaptation to climate change depending on the circumstances. Many baleen whales show philopatry to feeding grounds and are also capital breeders that meet migratory and reproductive costs through seasonal energy intake. Southern right whales ( Eubalaena australis, SRWs) are capital breeders that have a strong relationship between reproductive output and foraging success. The population dynamics of South Africa's population of SRWs are characterized by two distinct periods: the 1990s, a period of high calving rates; and the late 2010s, a period associated with lowered calving rates. Here we use analyses of stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope values from SRW biopsy samples ( n  = 122) collected during these two distinct periods to investigate foraging ecology of the South African population of SRWs over a time period coincident with the demographic shift. We show that South African SRWs underwent a dramatic northward shift, and diversification, in foraging strategy from 1990s to 2010s. Bayesian mixing model results suggest that during the 1990s, South African SRWs foraged on prey isotopically similar to South Georgia/Islas Georgias del Sur krill. In contrast, in the 2010s, South African SRWs foraged on prey isotopically consistent with the waters of the Subtropical Convergence, Polar Front and Marion Island. We hypothesize that this shift represents a response to changes in preferred habitat or prey, for example, the decrease in abundance and southward range contraction of Antarctic krill. By linking reproductive decline to changing foraging strategies for the first time in SRWs, we show that altering foraging strategies may not be sufficient to adapt to a changing ocean. Abstract : Southern right whales ( Eubalaena australis, SRWs) are migratory capital breeders with a strong relationship between reproductive output on coastal wintering grounds and foraging success in the Southern Ocean. During the 1990s, South African SRW foraged on prey isotopically similar to South Georgia/Islas Georgias del Sur krill and showed high population growth. In contrast, the 2010s show a shift to foraging around the Subtropical Convergence, Polar Front and Marion Island, concomitant with a slow in population growth. This link suggests that altering foraging strategies may not be sufficient to adapt to a changing ocean.